6(n-1)=4n+8

Simple and best practice solution for 6(n-1)=4n+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(n-1)=4n+8 equation:


Simplifying
6(n + -1) = 4n + 8

Reorder the terms:
6(-1 + n) = 4n + 8
(-1 * 6 + n * 6) = 4n + 8
(-6 + 6n) = 4n + 8

Reorder the terms:
-6 + 6n = 8 + 4n

Solving
-6 + 6n = 8 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-6 + 6n + -4n = 8 + 4n + -4n

Combine like terms: 6n + -4n = 2n
-6 + 2n = 8 + 4n + -4n

Combine like terms: 4n + -4n = 0
-6 + 2n = 8 + 0
-6 + 2n = 8

Add '6' to each side of the equation.
-6 + 6 + 2n = 8 + 6

Combine like terms: -6 + 6 = 0
0 + 2n = 8 + 6
2n = 8 + 6

Combine like terms: 8 + 6 = 14
2n = 14

Divide each side by '2'.
n = 7

Simplifying
n = 7

See similar equations:

| 3t-3=2t+6 | | 3x+1=x-13 | | x-6=33 | | 6/11-3/11 | | 1=-2/3(x-6) | | X/x-4+8=4/x-4 | | 4(3x-3)-3(2x-4)=0 | | 1=-2/3(x-1/6) | | X+3(5+3x)=95 | | 64x^2-112x=0 | | 3/8+5/12 | | (4x+5)(x^2+2x-8)=0 | | .24(57.5)+.17y=17.8 | | 3x+6.84=2x | | -7+-24= | | 3/10-1/4 | | 29-(x+6)=9x-7 | | 3r+8=20 | | 4*(x+2)=18 | | -17=p+3-3p | | 9y-12-4y+9=0 | | 12+9x-6x-19= | | c(c-5)=14 | | 8y-14-4y+9=0 | | 5.3=z-2.7 | | 4x=x-25 | | 6(w+1)=2(w+5) | | 4-3x-10=-18 | | -6(1-5x)+x=2x-35 | | a^2+30a-4000=0 | | 11/x+5/x=4 | | 6(5x-5)+3(16-3x)-4(5x+1)=-1 |

Equations solver categories